Bolzano merchants’ archive between 17th and 19th century: - Chiara Meluzzi (Quaderns d'Italià)
At the crossroad between German and Italian worlds, merchants in Bolzano (South Tyrol, Italy) played a crucial role in promoting multilingualism. This work will explore the language management of merchants’ life as emerging from the documents of their official institution, the so-called Magistrato Mercantile (1635-1851). For this first linguistic survey, a sub-set of documents has been selected from 1736 to 1740/1, in order to illustrate how multilingualism was applied in the everyday life of the Magistrato Mercantile, and how language alternation was used on specific occasions for specific purposes. In particular, it will be shown how acts were written in all four languages used in the Magistrato (i.e., Italian, German, Latin, and French), but how glosses were essentially in one language or another, without internal code-mixing.